Những vì sao đất nước Truyện danh nhân lịch sử Việt Nam - Nguyễn Anh (Loại sách danh nhân Việt Nam, 1975)
Truyện về các danh nhân lịch sử: Mai Thúc Loan, Ngô Quyền, Trần Quang Khải, Nguyễn Biểu, Trần Nguyên Hãn, Lê Hữu Trác, Nguyễn Huệ, Bà Huyện Thanh Quan